Orientações didáticas para a realização de feira de ciências nas séries iniciais a partir das concepções de professores - Nayra Lucas Paoli (2017)
This work aimed to identify the conceptions of the teachers of the initial series of Basic Education on the preparation and assembly of a fair and, from this, to elaborate a material with pedagogical contributions that can help the teachers of this segment of education in the development of a science fair . For this, the focus of the analysis of this research was the role of the teacher in the planning in each phase of the process until the culmination that is the fair. The subjects that made possible the elucidation of the investigation are teachers of the initial series of Elementary Education of three educational institutions located in Belo Horizonte. The research was carried out based on the content analysis of the questionnaires answered by these teachers, in which the following categories were assigned: school, teacher and process, which aided in understanding the research. In addition, the study was supported by a theoretical framework aimed at the development of fairs, model and functionality, endorsed by authors such as, Wanderley, Lima, Mancuso, Ormastroni, Pavão, Silva; and also the training of the teachers involved, thus seeking to establish pedagogical guidelines that could help the fairs in the initial series of Basic Education. As a result of this research, an E-book was developed with guidelines for the development of a fair; underpinning the pedagogical practice proposed in theoretical and methodological foundations. All of these practices aim to make the science fair a relevant pedagogical instrument aimed at improving the quality of the teaching of the content of this discipline. It was possible to identify at the end of the research, some conformities in the data of the three studied institutions, such as: the period of culmination of the work, the use of different strategies for the accomplishment of the science activities for the fair and the importance of the development of fairs in the school environment in the initial grades, as they enable meaningful learning and the development of skills important for student training.